RISK FACTORS AND PATHOPHYSIOLOGICAL CHANGES IN THE ADENOTONSILLAR SYSTEM IN CHILDREN - Abdusamatova Iroda Ilkhamovna; Muminova Sevarakhon Islomjon qizi; Karshiboyeva Sarvinoz Shukurjonovna; Gapurova Kholiskhon Mumin qizi; Khasanova Feruza Serkabayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. The adenotonsillar system plays a crucial role in the immune defense of the upper respiratory tract, especially in early childhood. However, pathological hypertrophy and chronic inflammation of adenoids and palatine tonsils remain among the most prevalent ENT disorders worldwide. According to global epidemiological data, up to 30–50% of children aged 3–10 years suffer from varying degrees of adenotonsillar pathology, often associated with recurrent infections and environmental exposures. This study aims to analyze risk factors and morphological-functional changes in the adenotonsillar system and assess their clinical implications. A comparative clinical study involving 120 children (90 patients and 30 controls) was conducted using комплекс clinical, laboratory, and instrumental methods. The findings demonstrate a significant association between environmental, immunological, and infectious factors with adenotonsillar hypertrophy and dysfunction. The results highlight the importance of early diagnosis and targeted preventive strategies.